Diagnosing Calciphylaxis: A Review With Emphasis on Histopathology. (July 2020) - Bahrani, Eman; Perkins, Ifeoma U.; North, Jeffrey P.
Abstract : Abstract: Calciphylaxis is a cutaneous vasculopathy with high morbidity and mortality characterized by vascular intimal fibrosis, calcification, stenosis, thrombosis, and eventual tissue death due to ischemia. Histopathologic diagnosis is often difficult, frequently necessitating multiple tissues samples due to lack of specific histopathologic features and subtle changes on biopsies of early lesions. In this study, we review the reported clinical and histopathologic features of calciphylaxis, correlating them with relevant imaging, ancillary studies, and pathophysiology. Although many histopathologic changes seen in calciphylaxis are also reported in other conditions (eg, Mönckeberg sclerosis, lupus panniculitis, pancreatic panniculitis, and peripheral artery disease), calcification of subcutaneous small vessels, thrombosis and/or ischemic changes, pseudoxanthoma elasticum–like changes in the subcutis, and perieccrine calcification may serve as helpful clues. von Kossa and Alizarin red stains can assist in the identification of subtle calcification. Netlike calcification of the affected blood vessels on imaging further supports the diagnosis. Studies into the pathophysiology of calciphylaxis are ongoing and will hopefully facilitate the development of additional diagnostic adjuncts to increase sensitivity and specificity for the diagnosis of this disease.